THE COMPARISON BETWEEN GRAB AND GOJEK IN BANDAR LAMPUNG, INDONESIA - Puteri Nuraliah Binti Raja Afandi; Siti Muzainah binti Mohamad Marzuki; Novita Sari (Proceeding International Conference on Information Technology and Business, 2019)
There are a lot of company that provide a service to customer. Through provide services, company can gain a lot of profit. Services are activities, which are offered for sale or are provided in connection with sales of goods. Services are intangible, difficult to attain quality standard and it involves expenditure without tangible return benefit. Therefore, the researcher had choose topic “The Comparison between Grab and Gojek “. This is because both provide services to their customer. The purpose this research is to identify how the seven tools marketing mix used to compare between Grab and Gojek. The researcher measured the information about both application by using marketing mix, which is product, price, place, promotion, process, people and physical evidence. Besides, there are surveys that the researcher already made to gain a lot of feedback from the respondent who are using both transportation. The survey form have been given to 100 respondents randomly in Bandar Lampung, Indonesia. The questions are provide by using google form. Even though, Grab and Gojek look similar but there have differentiation between both applications. The researcher will identify the SWOT analysis for both. Grab and Gojek should know how to overcome their weaknesses and ensure that their services remain the choice and loyalty of their customers.Keywords: comparison, Grab, Gojek, SWOT